Study on the Suitability Analysis of the Use of Floating Breakwaters in Palipi Fishing Port - Paotonan, Chairul; Paroka, Daeng; Rahman, Sabaruddin; Ashury, Ashury; Assidiq, Fuad Mahfud; Azisah, Nur (Department of Naval Architecture - Diponegoro University, 2024)
Palipi Fishing Port is a fish landing port with the condition of the dock building facing directly to the open sea without any protection of the port pond. This causes fishermen to be afraid to anchor their ships at Palipi Harbor, especially during the west season. In addition, the condition of the soil bearing capacity at the seabed due to thick sediment deposits in the harbor water area makes it difficult to apply a pile-type breakwater. Therefore, in order to function optimally, Palipi Fishing Port needs to immediately have a breakwater that is suitable for its geographical conditions as a protection from ocean waves. Floating breakwater is the solution due to its floating structure and efficient in reducing waves. This research will identify the suitability between wave occurrence at Palipi Fishing Port and the effectiveness of using floating breakwater while still considering the ease of development so that it is expected that the port can function optimally for regional economic development.